Tuvan folklore in the years of People’s Republic of Tuva - Orus-ool, Svetlana M. (The New Research of Tuva, 2016)
The article looks at the early stages of Tuvan folklore studies. Its roots go back to the 19th century when Tuvan folklore was collected and analyzed by Russian orientalists, scholars and travelers, such as V.V. Radlov, G.N. Potanin, N.F. Katanov, F.Ya. Kon, etc. They wrote down and later published samples of almost all genres of Tuvan folklore. Since these invaluable notes laid the foundation for studying Tuvan folklore and literature, it is important to take a closer look at the materials collected in this period (Most of them have been published in the “Uriankhai. Tyva depter’ anthology (Moscow, 2007-2009)).After the People’s Republic of Tuva declared independence in 1921, a new stage in Tuvan folklore studies has begun. It was in this period that alongside with collecting new material, folklore studies began as a truly scholarly discipline after the new system of writing was introduced. The first research and cultural institutions, such as the Scholarly and Press Committee at the PRT Cabinet of Ministers (the predecessor of Tuva Research Institute for Language, Literature and History (TNIIYaLI)), devoted themselves to collecting, studying and publishing Tuvan folklore. Regional newspapers called upon their readers to help write down old legends, folk songs and tales. Folklore texts found their way into the first ABCs and textbooks for Tuvan schools, as well as into specialized folklore anthologies. In 1939 the first book on literary and folklore studies appeared – S. Piurbiu’s ‘Anyiak chogaalchylarga duza’ (A young writer’s adviser). It aimed to help young authors and critics understand the terminology and genre systems of both literary fiction and folklore.Our study is based on the analysis of contemporary reprints of early 20th century texts and collections, as well as research articles, general audience scholarship, folklore anthologies, newspaper articles and other texts published in the People’s Republic of Tuva.
Keywords: People’s Republic of Tuva (PRT); «Uriankhai. Tyva depter»; folklore texts; folklore studies in Tuva; Scholarly Committee; mass media; history of Tuva